Concurrence of leukocyte chemotactic factor 2-associated amyloidosis and autoimmune diseases: A case report - Wang, Shuang; Yu, Xiao-juan; Li, Dan-yang; Xu, Jin; Wang, Su-xia (Frontiers in Immunology, 2022)
Leukocyte chemotactic factor 2-associated (ALECT2) amyloidosis is one of the recently reported types of amyloidosis, which is caused by the extracellular deposition of leukocyte chemotactic factor 2 (LECT2). There have not been any reports involving the concurrence of ALECT2 amyloidosis with Sjögren’s syndrome (SS) or systemic lupus erythematosus (SLE)s. Herein, we report a case of a 68-year-old Chinese woman presenting with long duration of sicca symptoms. The clinical evaluation and laboratory findings showed that she had SS overlapped with SLE. Kidney biopsy revealed a membranoproliferative glomerulonephritis (MPGN) with glomerular deposition of dominant IgG3-kappa by immunofluorescene, which was related to SS/SLE. Furthermore, patchy congophilic amyloid deposits in the tubulointerstitium were detected, which were positive for LECT2 protein by immunohistochemical staining and immunoelectron microscopy. This is the first case of ALECT2 amyloidosis that coexisted with SS/SLE, and the causal relationship between ALECT2 amyloidosis and autoimmune diseases remain unclear.